2021
DOI: 10.1186/s12915-021-01082-5
|View full text |Cite
|
Sign up to set email alerts
|

Age-related susceptibility to insulin resistance arises from a combination of CPT1B decline and lipid overload

Abstract: Background The skeletal muscle plays a central role in glucose homeostasis through the uptake of glucose from the extracellular medium in response to insulin. A number of factors are known to disrupt the normal response to insulin leading to the emergence of insulin resistance (IR). Advanced age and a high-fat diet are factors that increase the susceptibility to IR, with lipid accumulation in the skeletal muscle being a key driver of this phenomenon. It is debated, however, whether lipid accumu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 65 publications
10
26
0
Order By: Relevance
“…To explore the reasons for this, the investigators found increased fat accumulation in muscle and liver tissue as assessed by 1H NMR spectroscopy and an approximately 40% reduction in mitochondrial oxidative and phosphorylation activity as assessed by in vivo 13C/31P NMR spectroscopy ( 118 ). According to the result of an animal experiment, compared with young mice, aged mice are more susceptible to IR, due to reduced levels of glycolytic proteins and reduced flexible to diet, caused by reduced mitochondrial β-oxidation capacity ( 119 ). However, these hypotheses still need to be further tested and further understanding of the metabolic changes associated with aging.…”
Section: Pathogeny Of Irmentioning
confidence: 99%
“…To explore the reasons for this, the investigators found increased fat accumulation in muscle and liver tissue as assessed by 1H NMR spectroscopy and an approximately 40% reduction in mitochondrial oxidative and phosphorylation activity as assessed by in vivo 13C/31P NMR spectroscopy ( 118 ). According to the result of an animal experiment, compared with young mice, aged mice are more susceptible to IR, due to reduced levels of glycolytic proteins and reduced flexible to diet, caused by reduced mitochondrial β-oxidation capacity ( 119 ). However, these hypotheses still need to be further tested and further understanding of the metabolic changes associated with aging.…”
Section: Pathogeny Of Irmentioning
confidence: 99%
“…Fractional distributions of [6,6-2 H 2 ]-glucose and [U- 13 C]-glucose in bloodspots were measured according to van Dijk et al (38). Glucose was converted into its pentaacetate derivative by adding pyridine/acetic anhydride mixture.…”
Section: Gas Chromatography Coupled To Mass Spectrometry (Gc-ms) and ...mentioning
confidence: 99%
“…The copyright holder for this preprint this version posted March 21, 2023. ; https://doi.org/10.1101/2023.03.18.533083 doi: bioRxiv preprint insulin resistance was aggravated by age (13). The studies differ, however, in terms of (i) diet duration, timing and composition, and (ii) mouse strain.…”
Section: The Computational Model To Analyze the Tracer Ogtt Was Inspi...mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, decreased activity of AMPK may in turn accelerate the process of ageing. Of note, ageing is also a susceptible factor of insulin resistance ( Vieira-Lara et al, 2021 ). Thus, it is speculated that the decline of AMPK activity during ageing may also participate in the occurrence and development of insulin resistance and DM.…”
Section: Amp-activated Protein Kinase In the Pathophysiology Of Intervertebral Disc Degenerationmentioning
confidence: 99%